2020
DOI: 10.7882/az.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone citizen science for turtles: identifying motives, usage patterns and reasons why citizens stop participating

Abstract: Citizen science has become popular for data collection in ecology and environmental management. However, most participants in citizen science projects are only involved for a short period of time. Understanding the reasons behind this dropout rate is important for improving long term participation. Here we investigated participation rates in TurtleSAT, an Australian turtle mapping app aimed at collecting data useful for conservation efforts. First, we looked at the TurtleSAT database to examine the number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, we found that this type of citizen science still has the potential to inspire positive change despite its limitations, and could be improved by strategically including learning objectives in the data collection process. Creating a more direct link between social media, the project's website and the scientific literature might render information more accessible (Santori et al., 2020). Organising workshops on specific scientific skills, such as species identification, might support the skill improvement that currently is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that this type of citizen science still has the potential to inspire positive change despite its limitations, and could be improved by strategically including learning objectives in the data collection process. Creating a more direct link between social media, the project's website and the scientific literature might render information more accessible (Santori et al., 2020). Organising workshops on specific scientific skills, such as species identification, might support the skill improvement that currently is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A separate set of questions within the same questionnaire was analysed in Santori et al. (2020) to determine the reasons why participants left the TurtleSAT app after initial use.…”
Section: Methodsmentioning
confidence: 99%
“…Mobile apps have played a positive role in citizen science projects, but the cost of regular software maintenance and management, maintaining volunteer enthusiasm, and the persistence of report data are challenges with using mobile apps (Liebenberg et al 2017;Hann et al 2018;Andrachuk et al 2019;Santori et al 2020). For the time being, community-based approaches can be somewhat easier to manage by directly engaging the interest of citizen scientists and obtaining positive feedback.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Santori et al . 2020). For the time being, community‐based approaches can be somewhat easier to manage by directly engaging the interest of citizen scientists and obtaining positive feedback.…”
Section: Discussionmentioning
confidence: 99%